Quantifying the effect of the facemask on helmet performance. (June 2018) - Rowson, Bethany; Terrell, Evan J; Rowson, Steven
Evaluating and improving helmet design play a crucial role in reducing sports-related concussions. Despite widespread use of facemasks by football and hockey players, no helmet standards currently exist to test helmets equipped with facemasks. The purpose of this study was to determine the effect that attached facial protection has on the head kinematics resulting from impacts to the helmet shell. Helmets were fit to a modified NOCSAE (National Operating Committee on Standards for Athletic Equipment) headform and subjected to blows from a pneumatic impactor. A total of 240 impact tests were performed to evaluate the effect of the facemask on four helmet models (two for football, two for hockey). For each helmet model, one sample was tested with a facemask and another without a facemask. Tests were conducted at two impact velocities (6, 9 m/s) and three impact locations (front, side, and rear boss) for a total of six impact conditions. Five trials were performed for each helmet sample at each condition. Two-factor analyses of variance were used to quantify effects on linear and rotational head acceleration and Severity Index due to impact location and facemask presence. Significant effects varied by helmet model and impact location and were more commonly associated with football helmets. Differences in facemask effects between sports are likely attributed to differences in facemask-shell attachment mechanisms, and differences in the structure of the facemask itself. The effects of the facemask on linear and rotational acceleration were small, approximately 5% for both football and hockey helmets. On average, peak accelerations were decreased with the addition of a facemask, but individual differences were mixed and varied by helmet type and impact location. These small differences would not greatly affect impact performance tests in the lab. The results of this study have direct applications toward helmet standard development.